2020
DOI: 10.1111/ced.14196
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, emotion dysregulation, attention deficit and psychiatric comorbidity in children and adolescents with vitiligo

Abstract: Background. To date there is limited literature on the prevalence of chronic skin conditions and its association with levels of physical activity (PA) in Spain. Aim. To determine the prevalence of chronic skin disease and to compare levels of PA between people with and without chronic skin disease in a large representative sample of Spanish adults aged 15-69 years. Methods. Data from the Spanish National Health Survey 2017 were analysed. Chronic skin disease was assessed using a yes/no question. PA was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…The sample sizes of participants ranged from 24 to 1432 people, and gender information was also presented. The mean age in all of the studies except for that by Ucuz et al [ 18 ] ranged from 24.6 to 47.1 years. Ten screening scales were applied to evaluate the prevalence of anxiety.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The sample sizes of participants ranged from 24 to 1432 people, and gender information was also presented. The mean age in all of the studies except for that by Ucuz et al [ 18 ] ranged from 24.6 to 47.1 years. Ten screening scales were applied to evaluate the prevalence of anxiety.…”
Section: Resultsmentioning
confidence: 98%
“…Six case-control studies reported data about the prevalence of anxiety in both vitiligo patients and healthy controls [ 9 , 10 , 18 21 ]. The pooled OR for the prevalence of anxiety between the two groups was 6.14 (95% CI: 3.35–11.24; P < 0.001), which demonstrated the association between anxiety and vitiligo.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations